2009
DOI: 10.1007/s00702-009-0224-y
|View full text |Cite
|
Sign up to set email alerts
|

Circulating immune complexes of Aβ and IgM in plasma of patients with Alzheimer’s disease

Abstract: It has previously been shown that immune complexes (IC) of a given biomarker with class M immunoglobulins (IgM) provide better performances compared to the unbound biomarker in a number of cancer entities. In the present work, we investigated IC of IgM-Ab as a potential biomarker for Alzheimer's disease (AD). Ab-IgM concentration has been measured in 75 plasma samples from patients with AD, individuals with mild cognitive impairment (MCI), and healthy age-and sexmatched controls (HC). To characterize the fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 58 publications
0
17
0
1
Order By: Relevance
“…While these antibodies may play a physiological role, they also pose a challenge for the development of blood-based diagnostics, i.e., unless efforts are undertaken to promote the dissociation of pre-existing Aβ-immunoglobulin complexes [ 32 ], their existence may add to variability in detection results by masking the true levels of Aβ in the blood [ 33 ]. Whereas most previous studies did not specifically investigate interactions between Aβ and IgM, one study documented the existence of IgM-Aβ complexes in blood but did not detect differences between MCI and AD samples [ 34 ]. However, the same authors subsequently reported a reduction of IgM auto-antibodies against pyro-glu Aβ [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…While these antibodies may play a physiological role, they also pose a challenge for the development of blood-based diagnostics, i.e., unless efforts are undertaken to promote the dissociation of pre-existing Aβ-immunoglobulin complexes [ 32 ], their existence may add to variability in detection results by masking the true levels of Aβ in the blood [ 33 ]. Whereas most previous studies did not specifically investigate interactions between Aβ and IgM, one study documented the existence of IgM-Aβ complexes in blood but did not detect differences between MCI and AD samples [ 34 ]. However, the same authors subsequently reported a reduction of IgM auto-antibodies against pyro-glu Aβ [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, IgM anti-Aβ autoantibodies are found in essentially all individuals, although in different concentrations [17], [18], [23]. These human IgM autoantibodies have previously been studied with the aim of identifying differences between healthy controls and individuals affected by mild cognitive impairment or AD [18], [23]. Differences in IgM auto-antibodies have been suggested as a potential diagnostic marker, as the levels of specific IgM auto-antibodies were lower in AD patients compared to controls [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, there appears to be a contribution from nonneuronal tissues and, more important, Aβ is bound to a variety of proteins in blood, and thus should be interpreted with caution when used for diagnosis, as discussed later [39]. …”
Section: Major Challenges In Blood-based Biomarker Development For Admentioning
confidence: 99%